As it Was in the Beginning : an Intertextual Analysis of New Creation in Galatians, 2 Corinthians, and Ephesians. - Owens, Mark D. ([Place of publication not identified] : Casemate Publishers and Book Distributors, LLC, 2016)
A new study of the concept of ""new creation"" in the Epistles of St Paul, setting it in the framework of Paul's understanding of the ""new exodus"" theme in Isaiah.
Vendor-supplied metadata.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Creation -- Biblical teaching; RELIGION -- Biblical Studies -- Paul's Letters; RELIGION -- Biblical Studies -- New Testament; Creation -- Biblical teaching; Electronic books; Criticism, interpretation, etc